PRESCRIPTION PATTERN ANALYSIS OF ANTIDEPRESSANTS IN PSYCHIATRIC OUTPATIENT DEPARTMENT OF TERTIARY CARE HOSPITAL IN INDIA - Chattar Kb; KARVE AV; SUBRAMANYAM A; TONDARE SB (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objectives: (1) To study the prescription pattern of antidepressants in treatment of depression in psychiatry outpatient department of tertiary care hospital in India, (2) to find the change in drug therapy during last 1 year of the treatment (old patients), (3) to study reason for a change in drug therapy, and (4) to calculate prescribed daily dose (PDD) of the individual drugs. Methods: It was cross-sectional single centered observational study with a sample size of 284 cases. Case record forms were filled from case paper. Results were analyzed. Results: Monotherapy was practiced in 259 patients, i.e., 91.19% of the study population. A maximum number of patients (n=159, 55.98%) received escitalopram monotherapy. Polytherapy was practiced in 25 (8.8%) patients. Out of 160 old cases, 9 patients required a change in drug therapy either in the form of drug or dose. PDD values were escitalopram: 12.30, fluoxetine: 18.43, paroxetine: 25, sertraline: 96.35, amitriptyline: 57.79, imipramine: 5.75, and mirtazapine: 17.67. Conclusion: From our study, it is concluded that the incidence of depression is more in females. Selective serotonin receptor inhibitors were the most common class of drugs used followed by tricyclic antidepressants. Escitalopram was most frequently prescribed antidepressant followed by amitriptyline. The prescription trend was toward monotherapy. Most patients continued treatment on the same medication. The poor therapeutic response was the most common reason for drug change. Keywords: Depression, Prescribed daily dose, Defined daily dose.